Profiles of Hepatitis B Virus Serological Markers among Asymptomatic Population in Anambra State, Southeastern Nigeria (2017)
Hepatitis B Virus (HBV) infection is apparent in endemic countries affecting millions of people. Further, the asymptomatic nature of the pathogen is a major public health concern. This study was designed to assess the burden of HBV by exploring the serologic markers of infection among consenting asymptomatic community dwellers in two cities in southeastern Nigeria. A total of 405 blood specimens were tested for HBsAg, anti-HBs, HBeAg, anti-HBe, total anti-HBc and anti-HBc-IgM using ELISA technique. Overall, 14(3.5%) of the participants had detectable HBsAg out of which 1 (7.1%) had HBeAg and 13, anti-HBe. Two of the HBsAg positives (14.3%) had detectable anti-HBc-IgM. A total of 144 (35.5%) had detectable anti-HBc, even as 65 (57.0%) of them had the marker as the only serologic evidence of HBV exposure. Thirty-seven (9.1%) participants had anti-HBs only although all of them were born before the start of the childhood HBV vaccination. Altogether, 224 (57.3%) had no detectable serological markers of HBV infection or immunity and were obviously at risk ofHBV infection. This study described various patterns of HBV serologic markers of infection in the study population and probable risk of viru spread. Our results support the need for urgent intervention and implementation of measures to control the spread of HBV infection in Nigeria.